Analysis Of The Influence Of Car, Npf, Fdr, Bopo And Inflation On Profitability (Case Of Islamic Banks In Bei For The 2016 To 2020 Period) - Siddik, Ibnu; Gursida, Hari; Hardiyanto, Arief Tri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The Covid-19 pandemic has indeed made the economy, including banking, experience a decline in performance. The impact of a pandemic is like the case of an economic recession, so banking management must be able to make the right strategy so that the effect is not too big. Banks (including Islamic banks) are more selective in providing loans (financing) because they compete with higher capital, liquidity and reserve requirements imposed since the global financial crisis, besides that there has also been a decline in economic activity. For this reason, research must be carried out to find out the effect of the economic crisis on the performance of Islamic banks such as CAR capital, NPF, FDR and Profitability. The research method used is associative quantitative research, namely research that asks the relationship between two or more variables. The relationship used in this study is a causal relationship. A causal relationship is a causal relationship, which consists of independent variables (variables that influence) and dependent (variables that are influenced). The results of the study show that the Capital Adequacy Ratio (CAR) has a positive effect on Profitability (ROA). The regression coefficient of the Capital Adequacy Ratio (CAR) is -0.020937 meaning that if the Capital Adequacy Ratio increases by 1% it will reduce Profitability (ROA) by -0.020937 assuming other variables are considered constant. Non-Performing Financing (NPF) partially has a positive effect on Profitability (ROA) in Islamic Commercial Banks listed on the IDX for the period 2016 to 2020. Financing to Deposit Ratio (FDR) has a positive effect on Profitability (ROA) and the results of data processing state that Financing to Deposit Ratio has a positive effect on Profitability (ROA) so hypothesis 3 is accepted. The regression coefficient of FDR is 0.065210 meaning that if the FDR increases by 1% it will increase ROA by 0.065210 assuming other variables are considered constant. Operational Costs and Operating Income (BOPO-Biaya Operasional Dan Pendapatan Operasional) have a negative effect on Profitability (ROA) and the results of data processing state that BOPO have a negative effect on Profitability (ROA), BOPO have increased by 1%, it will reduce ROA by -0.135394 assuming other variables are held constant. Inflation has a positive effect on Profitability (ROA) and the results of data processing state that Inflation has a positive effect on Profitability (ROA). if inflation increases by 1% it will increase Profitability (ROA) by 2.679569 assuming other variables are held constant.